When do people derogate or psychologically distance themselves from victims? Belief in a just world and ingroup identification. - Correia, I. (2014)
Two factors increase the threat for individuals' belief in a just world (BJW) posed by an innocent victim: the degree of the observer's explicit endorsement of BJW and the fact that the victim shares a common identity with the observer. In this paper, we aim to investigate whether or not these two factors (BJW and ingroup identification) have an interaction effect on each of two mechanisms that reduce the threat to BJW: victim derogation and psychological distancing from the victims. In two studies with university students we predicted and found that BJW interacted with identification with an ingroup victim to predict victim derogation (Study 1) and disidentification from the group shared with the victim (Study 2). In Study 1, the positive relationship between BJW and derogation was significant for strongly identified participants but not for weakly identified participants. In Study 2, high BJW was associated with low ingroup identification only when group salience was activated.